التقارير المالية ودورها في ترشيد القرارات الاستثمارية - دراسة حالة عينة من المستثمرين ببورصة الجزائر- (مجلة الواحات للبحوث والدراسات, 2017)
This Study Aims At Demonstrate The Impact Of Financial Reports In Rationalizing Investment Decisions, At A Time Where The World Is Experiencing An Economic Transformation And Global Variables That Become Characterized By Conditions Of Uncertainty And Risk, It Led To The Necessity For Disclosure Of A Set Of Accounting And Financial Information And This Is What Will Help In Making Investment Decisions.To Achieve The Objectives Of The Study The Questionnaire  Has Been Designed  To Collect The Information, Where It Was Distributed Toa Sample Of Investors, And Were Processed Using The Statistical Program SPSS.   The Study Has Concluded That There Is A Positive Impact With A Between Financial Reports And Rationalizing Investment Decisions. Key Words -  Financial Reports, Investment Decisions, A Sample Of Investors, Stock Exchange  Of Algeria